Comparison of the Recoil of Conventional and Electromagnetic Cannon - Edward M. Schmidt (Shock and Vibration)
The recoil from an electromagnetic (EM) railgun is discussed and compared with that from conventional, propellant gas driven cannon. It is shown that, under similar launch conditions, the recoil of the EM gun is less than that of the powder gun; however, use of a muzzle brake on a powder gun can alter this relative behavior.